Bidirectional causal associations between frailty measures and sleep disturbances: a two-sample Mendelian randomization study - Che L; Zang H; Bi Y; Wen B; Xu L (Nature and Science of Sleep)
Lu Che,* Han Zang,* Yaodan Bi, Bei Wen, Li Xu Department of Anesthesiology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100730, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Xu, Email pumchxuli@163.comBackground: Observational studies have demonstrated a strong association between sleep disturbances and frailty. However, the causality remains inconclusive. We aimed to investigate the bidirectional causal relationships between frailty measures and sleep disturbances employing a two-sample Mendelian randomization (MR) analysis.Methods: Two-sample MR analyses were performed based on large-scale genome-wide association studies (GWAS) of the European population for frailty index (FI) (N = 175,226), Fried Frailty Score (FFS) (N = 386,565), insomnia (N = 283,595), sleep duration (N = 445,966) and sleep apnea (N = 523,366). We conducted the causal estimates using the inverse variance-weighted method (IVW), with sensitivity analyses using MR-Egger, weighted median, weighted mode, and MR pleiotropy residual sum and outlier (MR-PRESSO) analysis. Cochran’s Q test was performed to assess heterogeneity.Results: We found that genetically predicted FI was associated with shorter sleep duration and sleep apnea. The genetically predicted FFS was associated with insomnia, shorter sleep duration, and sleep apnea. In the reverse direction analysis, genetic liability to insomnia, short sleep duration, and long sleep duration were associated with an increase in FI. Genetic liability to short sleep duration and long sleep duration were associated with an increase in FFS.Conclusion: Our study provided genetic evidence supporting the bidirectional causality between frailty measures and sleep disturbances. The findings contribute to the prevention and management of frailty and sleep disturbances.Keywords: frailty, sleep disturbances, Mendelian randomization, the elderly